Matrix-Assisted Autologous Chondrocyte Transplantation for Cartilage Regeneration in Osteoarthritic Knees: Results and Failures at Midterm Follow-up. (January 2013) - Filardo, Giuseppe; Vannini, Francesca; Marcacci, Maurilio; Andriolo, Luca; Ferruzzi, Alberto; Giannini, Sandro; Kon, Elizaveta
Background: Young patients with osteoarthritic knees are a challenging population because of a combination of high functional demands and limited indication for joint replacement. Purpose: To analyze the potential of the cartilage regenerative approach by documenting the results and failures of matrix-assisted autologous chondrocyte transplantation (MACT) at midterm follow-up. Study Design: Case series; Level of evidence, 4. Methods: Forty-four patients affected by cartilage lesions in osteoarthritic knees underwent MACT as a salvage procedure. The mean age at surgery was 42 years (range, 20-58 years), and the average defect size was 4 cm 2 (range, 1.5-9 cm 2 ). Patients were prospectively evaluated with the subjective International Knee Documentation Committee (IKDC), EuroQol visual analog scale (EQ-VAS), and Tegner scores preoperatively; at 1, 2, and 5 years; and at a final assessment at 9 years' mean follow-up. Adverse events and failures were also reported. Results: A statistically significant improvement was observed in all scores from the initial evaluation to the final follow-up. The mean ± standard deviation IKDC subjective score improved from 38.0 ± 15.8 to 67.0 ± 18.3 at 2 years ( P < .0005), with a subsequent decrease to 57.8 ± 20.6 at the final follow-up ( P = .012). The same trend was confirmed by the EQ-VAS score. The activity level revealed by the Tegner score improved at all follow-ups but without achieving the preinjury level. The analysis of the influencing factors showed the importance of the meniscus condition, revealing a significantly inferior outcome in knees with previous or combined partial meniscectomy procedures. During the study period, 12 patients had failed results, producing a cumulative failure rate of 27.3%. At the last evaluation, half of the patients considered their condition not better than before the treatment, and 39% would not repeat the treatment considering the results obtained. Conclusion: Despite a statistically significant improvement, the clinical outcome was poor. A higher improvement could be obtained in patients who had not undergone previous or combined meniscectomies, but this was limited over time. The failure rate was also high, regardless of the degree of osteoarthritis. Tissue-engineered cartilage implantation is questionable for this indication, and the limits of this scaffold-based procedure have to be considered if it is used as a salvage procedure for young patients affected by knee osteoarthritis.